1985
DOI: 10.1111/j.1365-2133.1985.tb02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukotrienes B4, C4 and D4 stimulate DNA synthesis in cultured human epidermal keratinocytes

Abstract: Leukotrienes in psoriatic skin lesions are potent mediators of inflammation. We have studied the capacity of leukotrienes to stimulate the DNA synthesis of cultured human epidermal keratinocytes. At concentrations ranging from 10(-12) to 10(-8) M, LTB4 produced a 100% increase of DNA synthesis determined both as the incorporation of [3H] thymidine and as the labelling index. In comparison, LTB4 had no effect on the DNA synthesis of dermal fibroblast cultures. 5S,12S-LTB4 and 5S,12S-all-trans-LTB4 did not chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(64 citation statements)
references
References 26 publications
2
62
0
Order By: Relevance
“…Although there is no published study on the effects of LTB 4 on human tendon fibroblasts, our results agree with previous reports obtained using other cell/tissue types. For example, LTB 4 was shown to stimulate DNA synthesis in cultured human epidermal keratinocytes at picomolar concentrations (Kragballe et al, 1985). Also, in arterial smooth muscle cells, LTB 4 at 10 pM was shown to stimulate cell proliferation and DNA synthesis (Palmberg et al, 1987(Palmberg et al, , 1989.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no published study on the effects of LTB 4 on human tendon fibroblasts, our results agree with previous reports obtained using other cell/tissue types. For example, LTB 4 was shown to stimulate DNA synthesis in cultured human epidermal keratinocytes at picomolar concentrations (Kragballe et al, 1985). Also, in arterial smooth muscle cells, LTB 4 at 10 pM was shown to stimulate cell proliferation and DNA synthesis (Palmberg et al, 1987(Palmberg et al, , 1989.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that exogenous addition of PGE 2 at a dose of 100 ng/ml decreases proliferation and collagen production in human patellar tendon fibroblasts (HPTFs) (Cilli et al, 2004). On the other hand, LTB 4 at picomolar concentrations has been shown to stimulate DNA synthesis in cultured human epidermal keratinocytes and to induce proliferation of arterial smooth muscle cells in primary culture (Kragballe et al, 1985;Palmberg et al, 1989). Also, leukotrienes at low concentrations (0.1 to 1 nM) stimulate collagen synthesis of lung fibroblasts (Phan et al, 1987(Phan et al, , 1988.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum effect of the leukotrienes was about half of that obtained with PDGF, and at suboptimal concentrations of PDGF, an additive effect of the leukotrienes was obtained. 341 Growth-promoting effects of leukotrienes have also been observed in cultures of glomerular epithelial cells, 3 4 2 3 4 3 epidermal keratinocytes, 344 fibroblasts, 345 and endothelial cells. 346 In recent experiments, we have continued to examine the growth-stimulatory effect of LTB 4 on rat aortic smooth muscle cells, with particular emphasis on the role of endogenous cyclooxygenase products (unpublished observations).…”
Section: Role Of Prostaglandins and Leukotrienesmentioning
confidence: 94%
“…A critical role of neutrophils in driving the hyperproliferation in the flaky skin mouse mutant has been demonstrated, and it is possible that neutrophils will prove to play a similar role in K5-I B␣ mice (22). It is known that neutrophils produce reactive oxygen species, lipid mediators, and proteolytic enzymes that potentially can affect keratinocyte proliferation (23)(24)(25). Of interest is also the infiltration of B220(ϩ) Pax5(Ϫ) cells with dendritic morphology, which we identify as plasmacytoid dendritic cells.…”
Section: Discussionmentioning
confidence: 99%